2001
DOI: 10.1126/science.1058379
|View full text |Cite
|
Sign up to set email alerts
|

Ventroptin: A BMP-4 Antagonist Expressed in a Double-Gradient Pattern in the Retina

Abstract: In the visual system, the establishment of the anteroposterior and dorsoventral axes in the retina and tectum during development is important for topographic retinotectal projection. We identified chick Ventroptin, an antagonist of bone morphogenetic protein 4 (BMP-4), which is mainly expressed in the ventral retina, not only with a ventral high-dorsal low gradient but also with a nasal high-temporal low gradient at later stages. Misexpression of Ventroptin altered expression patterns of several topographic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 20 publications
9
168
0
Order By: Relevance
“…4E). We have further shown that they indeed repress BMP signaling activities in human 293T cells when overexpressed, which is consistent with published results (46,47) (Fig. S6 B-H).…”
Section: Notch2 Represses the Expression Of Two Bmp Signaling Inhibitorsupporting
confidence: 93%
“…4E). We have further shown that they indeed repress BMP signaling activities in human 293T cells when overexpressed, which is consistent with published results (46,47) (Fig. S6 B-H).…”
Section: Notch2 Represses the Expression Of Two Bmp Signaling Inhibitorsupporting
confidence: 93%
“…Bmp signaling is essential for lens development and is involved in retinal differentiation (67)(68)(69)(70). Although a role for Bmps has been suggested in adult retinal pigment epithelium (71), little is known about Bmp and Smad pathways in the mature retinal photoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery that activated Smads can associate with the Drosha complex and regulate its activity suggests a possible mechanism by which this could occur. Given the known role of BMP/TGFbeta signaling in regulating various aspects of retinal development (Davis et al, 2000;Sakuta et al, 2001;Kim et al, 2005), this may be a possible mechanism of action for these factors that bears investigating.…”
Section: Regulated Processing Of Retinal Pri-mirnas?mentioning
confidence: 99%